Semantic access to streaming and static data at Siemens - Kharlamov, E; Mailis, T; Mehdi, G; Neuenstadt, C; Özçep, Ö; Roshchin, M; Solomakhina, N; Soylu, A; Svingos, C; Brandt, S; Giese, M; Ioannidis, Y; et al. (Elsevier, 2017)
We present a description and analysis of the data access challenge in Siemens Energy. We advocate Ontology Based Data Access (OBDA) as a suitable Semantic Web driven technology to address the challenge. We derive requirements for applying OBDA in Siemens, review existing OBDA systems and discuss their limitations with respect to the Siemens requirements. We then introduce the Optique platform as a suitable OBDA solution for Siemens. The platform is based on a number of novel techniques and components including a deployment module, BootOX for ontology and mapping bootstrapping, a query language STARQL that allows for a uniform querying of both streaming and static data, a highly optimised backend, ExaStream, for processing such data, and a query formulation interface, OptiqueVQS, that allows to formulate STARQL queries without prior knowledge of its formal syntax. Finally,we describe our installation and evaluation of the platform in Siemens.